Need for intensive care for neonates born between 29 and 34 weeks inclusive gestation. Issue 2 (29th January 2013) - Lutz, Tracey; Buckmaster, Adam; Bowen, Jennifer; Kluckow, Martin; Wright, Ian
<x xml:space="preserve">Abstract</x> Aims To identify the proportion of preterm infants needing neonatal intensive care (NIC) between 29 and 34 weeks gestation. To identify any associated risk factors. Methods This population‐based study identified all babies, born without congenital abnormalities, between 29 and 34 weeks gestation inclusive. A 21‐month period ending September 2009 was used. The need for NIC was defined using specific cardiorespiratory and nutritional criteria. The use of continuous positive airway pressure alone was not included as a need for NIC. Data were extracted from a neonatal clinical database and individual medical records. Results Complete data were available from 707 out of 709 eligible infants born in the study period. The percentage of infants requiring cardiorespiratory support varied from 39 to 2.7% at 29 and 34 weeks, respectively. If nutritional criteria were included, this increased to 77% at 29 weeks and 7.2% at 34 weeks. Multivariate analysis determined that gestational age and delivery by Caesarean section increased the need for intensive care (P‐value <0.01). Antenatal steroids, gender, underlying maternal medical conditions, being small for gestational age or twin pregnancy had no statistically significant impact. Conclusions This study supports the National Health and Medical Research Council Guidelines of in‐utero transfer at <33 weeks gestation. Gestational age and delivery by Caesarean section remain major indicators for the need for NIC. In special care nurseries that have the capability and expertise to use nasal continuous positive airway pressure, the main indication for NIC is for nutritional support.